2022
DOI: 10.1111/nph.18157
|View full text |Cite
|
Sign up to set email alerts
|

Carbon allocation to root exudates is maintained in mature temperate tree species under drought

Abstract: Carbon (C) exuded via roots is proposed to increase under drought and facilitate important ecosystem functions. However, it is unknown how exudate quantities relate to the total C budget of a drought-stressed tree, that is, how much of net-C assimilation is allocated to exudation at the tree level.We calculated the proportion of daily C assimilation allocated to root exudation during early summer by collecting root exudates from mature Fagus sylvatica and Picea abies exposed to experimental drought, and combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 72 publications
(127 reference statements)
1
23
0
Order By: Relevance
“…The initial fine‐root biomass (mg cm −3 ) was determined with fine roots taken from 10 soil cores (diameter of 1.4 cm) within the first 10 cm of the uppermost soil layers on day −7. Because the biomass values of the two labeled plots differed from all other sampled plots and the previous years, the average initial biomass of all control and recovery plots of the experimental site, which agrees to fine‐root area values of Brunn et al (2022) on the same site and year, was accounted for further calculations. To calculate the fine‐root biomass at 10–30 cm depth and thus the total initial fine‐root biomass from 0 to 30 cm soil depth ( M FR30 ), a root biomass ratio between upper (0–10 cm) and lower (10–30 cm) soil layer was used, measured in summer 2018 on the same plots (Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial fine‐root biomass (mg cm −3 ) was determined with fine roots taken from 10 soil cores (diameter of 1.4 cm) within the first 10 cm of the uppermost soil layers on day −7. Because the biomass values of the two labeled plots differed from all other sampled plots and the previous years, the average initial biomass of all control and recovery plots of the experimental site, which agrees to fine‐root area values of Brunn et al (2022) on the same site and year, was accounted for further calculations. To calculate the fine‐root biomass at 10–30 cm depth and thus the total initial fine‐root biomass from 0 to 30 cm soil depth ( M FR30 ), a root biomass ratio between upper (0–10 cm) and lower (10–30 cm) soil layer was used, measured in summer 2018 on the same plots (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Root exudates were collected according to the method described by Phillips et al (2008) and Brunn et al (2022). Excavated root branches were rinsed with a nutrient solution (0.5 mM NH 4 NO 3 , 0.1 mM KH 2 PO 4 , 0.2 mM K 2 SO 4 , 0.15 mM MgSO 4 , 0.3 mM CaCl 2 ) after attached soil was gently removed with tweezers.…”
Section: Methodsmentioning
confidence: 99%
“…Low soil water availability, which can occur during drought or warming, is known to commonly reduce photosynthesis via stomatal closure, an adjustment that limits transpirational water loss (Chaves et al, 2003; Flexas et al, 2004). Our understanding of how global changes affect belowground plant carbon dynamics is much more limited, but studies of plant carbon allocation reveal the important role of belowground processes and signal the need for whole plant and system perspectives (e.g., Adair et al, 2009; Brunn et al, 2022; Chandregowda et al, 2022 in this issue; Hasibeder et al, 2015; Lyu et al, 2021; Pausch & Kuzyakov, 2018).…”
Section: Figurementioning
confidence: 99%
“…Additionally, further studies are needed to determine how climate change may differentially affect above and belowground plant responses across species, plant functional types, and developmental stages, and how shifts in carbon allocation influence long‐term soil carbon storage. How climate change impacts root carbon export, which affects soil organic matter, is particularly poorly understood, but advances in isotopic methods and in‐situ root exudation measurements make it possible to quantify and upscale rhizodeposition (Brunn et al, 2022; Pausch & Kuzyakov, 2018; Phillips et al, 2008). Root carbon dynamics could be especially important to investigate in systems like grasslands and arctic tundra where a majority of plant biomass occurs belowground (Iversen et al, 2015; Pastore et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…Based on the optimal partitioning theory, more C would be allocated to root under drought stress to improve water potential (Karlowsky et al 2018;Schönbeck et al 2021;Brunn et al 2022). However, our data indicated that S. moorcroftiana decreased C allocation to root in response to drought stress, both in terms of the absolute 13 C amount in root and the relative proportion within plants (Fig.…”
Section: Effects Of Drought and Nutrient De Cit On Plant Internal C A...mentioning
confidence: 99%